ORGANIZATION OF VIRTUAL ROBOTICS CLUBS ON THE BASIS OF SOFTWARE RELATED TO ROBOTICS - G Yo Buronova; S S Elmurodova; N J Juraqulov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstarct: today, the development of the digital economy is considered as the most important factor for the future. The use of robots in the production leads to very high financial efficiency and several times the acceleration of development. In this regard, it is very important to start the teaching of the elements of robotics from the elementary classes of general secondary schools.In this article, it is explained in detail that the use of virtual didactic tools in the organization of "robotics" circles in the primary classes of the general secondary school will give effective results.